Postopek oblikovanja varnostne kulture - poti in pasti - Levovnik, David (Delo in varnost, 2012)
The paper deals with the importance of a good safety culture and its impact on ensuring safety in organizations. The high safety culture is essential for ensuring health and safety at work. The first part describes the impact of safety culture on the high-tech, well defended systems, the dangerous cultural adaptations are considered. One section is also devoted to traps and driving forces that are present in hazardous tasks. The essential, basic elements - foundations of a good safety culture are presented. The second part presents an analysis, which is based on comparison of accidents at work, between Slovenia and Great Britain. Accidents are being compared by country and industry in which they have occurred. In the third and also the final part, the paper presents the results of analysis of safety culture in organizations, which was conducted on the begining of 2012 on a sample of Slovenian organizations. The findings and conclusions gained from those analyses are given.
Keywords: safety culture; varnostna kultura; accidents at work; nezgode pri delu; organizacijski dejavnostiki; organizational factors; health and safety at work; varnost in zdravje pri delu